The Correlation Between Students Achievement In Vocabulary And Speaking Ability at Grade 8 Junior High School Students - Zulfiana, Rifda (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2022)
ABSTRACT This research aimed to find out the correlation between students’ vocabulary mastery and speaking ability at grade 8 of SMP Negeri. This research was quantitative research which used correlational technique design. The sample of the research was 30 students of grade eight selected by clustering sampling. The instruments used in the research were vocabulary test and speaking test. Vocabulary test consisted of 50 questions of multiple choices, and speaking test in the form of role play. The research data were in the form of interpretation of students’ vocabulary and speaking test results, and their correlation. Based on data analysis, it was found that students’ vocabulary mastery and speaking ability were fair. They were proved by the mean score 65 for vocabulary mastery and 68 for speaking ability. Moreover, there was strong correlation between students’ vocabulary mastery and speaking ability. It was shown by the rvalue = 0,703 . Keywords:Students’ Achievement, Vocabulary, Speaking